A Review of Artificial Intelligence Adoptions in the Media Industry. Issue 3 (2nd October 2019) - Chan-Olmsted, Sylvia M.
ABSTRACT: Artificial intelligence is a transformational technology of the digital age and an increasingly critical business mindset for companies, especially for those in the media sector with a growing array of digital content products and advertising opportunities. Given its unique market characteristics, it is unclear whether AI would offer the same disruptive power and utilities in the media sector as in other tangible goods industries. This review examines the utilities of AI in the media industry, AI's role in the context of value chain, and the challenges in incorporating the cognitive technologies in this industry. It was concluded that AI applications in media have occurred in the eight main areas: audience content recommendations/discovery, audience engagement, augmented audience experience, message optimization, content management, content creation, audience insights, and operational automation. There are significant challenges in balancing the effectiveness and efficiency, and human and AI judgement.